Magnetic susceptibility of a two-dimensional electron gas in the strong magnetic field limit and for non-zero temperatures - Wang, Lipo. (2012)
Analytic expressions are derived for the magnetic susceptibility and the Fermi energy of a non-interacting two-dimensional electron gas in the strong field limit and for non-zero temperatures. The results at zero temperature agree with existing calculations but the results at finite temperature are different from those obtained recently by other authors.